What psychiatry left out of the DSM-5 historical mental disorders today - Shorter, Edward 1941- (Routledge, 2015)
Psychiatry as a field is over two centuries old and over that time has gathered great wisdom about mental illnesses. But there are diagnoses that the Diagnostic and Statistical Manual of Mental Disorders (DSM) failed to include, along with diagnoses that should not have been included, but were. Today we have diagnoses such as "schizophrenia" and "bipolar disorder" that do not correspond to the diseases found in nature; we have also left out disease labels that on a historical basis may be real. Shorter proposes a history-driven alternative to the DSM.